THE COACERVATION PROCESS OF MILK PROTEINS, SOLIDS AND LIPIDS, INDUCED BY CHITOSAN - Oksana Gennadievna Skorykh; Ludmila Ruslanovna Alieva; Ivan Alekseevich Evdokimov (Вестник Северо-Кавказского федерального университета)
The purpose of this work is development of technology of milk protein-fat concentrate with use of a natural coacervation agent - polysaccharide chitosan. The subject of the research is chitosan, cream, whey. During the experiments, the complexing ability of chitosan to the components of milk, proteins and lipids is also, and the process of coacervation with the use of gel-chitosan, with the different molecular mass,was studied. Characteristics of the coacervate and optimal fractional conditions were analyzed.